Acute impact of autoregulation of applied blood flow restriction pressures on bilateral single-joint upper limb resistance exercise - Rolnick, N.; De Queiros, V. S.; Moghaddam, M.; Marquette, L.; Taylor, S.; Walters, J.; Fedorko, B.; Werner, T. (Journal of Sports Sciences, 2025)
To investigate the acute effects of 4 sets of autoregulated (AR-BFR) versus non-autoregulated (NAR-BFR) applied pressures during blood flow restriction (BFR) resistance exercise to volitional failure compared with low-load exercise without BFR. A randomized crossover design study was conducted on 32 healthy adults (20.8 ± 2.3 years; 11 females). Outcome measures were as follows: (1) arterial stiffness, (2) peak perceptual responses and likelihood to perform again, and (3) performance. Results: Post-exercise changes in central and brachial diastolic blood pressure were decreased in all groups. Post-exercise supine systolic blood pressure in no-BFR increased (mean difference (MD) = 4 ± 1 mmHg, 95% CI (1-7), p = 0.003, n2 = 0.13). Total repetitions performed and volume workload were similar between BFR conditions but less than no-BFR. AR-BFR reported significantly higher exertion (MD = 0.53 ± 0.2, 95% CI (0.04-1.0), p = 0.03, n2 = 0.19) than other conditions, and induced greater discomfort (MD = 2.50 ± 0.36, 95% CI (1.63-3.37), p < 0.001, n2 = 0.28) than no-BFR. Conclusion: Biceps curl exercise to volitional failure appears to induce negligible arterial stiffness or blood pressure changes regardless of the application of autoregulation, yet autoregulation appears to enhance the perceptual response to BFR exercise compared to NAR-BFR without impacting exercise performance.